1988
DOI: 10.1128/jb.170.10.4451-4457.1988
|View full text |Cite
|
Sign up to set email alerts
|

Nucleotide sequence and expression of a Streptomyces griseosporeus proteinaceous alpha-amylase inhibitor (HaimII) gene

Abstract: The coding region of the alpha-amylase inhibitor (HaimIl) gene from the producing strain Streptomyces griseosporeus YM-25 was localized on an 800-base-pair DNA segment. The nucleotide sequence of a 1,191-base-pair region including the HaimIl gene was determined by the dideoxy-chain termination method. The nucleotide sequence data predicted an open reading frame of 363 base pairs starting with an ATG initiation codon and ending with a TGA translational stop codon. The amino acid sequence deduced from the nucleo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
0

Year Published

1989
1989
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(8 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…There is clearly synthesis and secretion of tendamistat in yields similar to those from pIJ702, from which vector pIJ486 was derived (Fig. 2B) (32 (24). Boxed in the nucleotide sequences are putative ribosomal-binding sites.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…There is clearly synthesis and secretion of tendamistat in yields similar to those from pIJ702, from which vector pIJ486 was derived (Fig. 2B) (32 (24). Boxed in the nucleotide sequences are putative ribosomal-binding sites.…”
Section: Resultsmentioning
confidence: 97%
“…Additionally, we show that the nucleotide sequence and the processing of tendamistat are significantly different to those of Haim II of Streptomyces griseosporus, whose primary and secondary protein structures are similar to those of tendamistat (1,24).…”
mentioning
confidence: 99%
“…These inhibitor-amylase interactions will offer a model for the study of specific protein-protein interactions. Our previous study about chemical modification of Haim showed that the arginine residue (equivalent to Arg (17) in T-76 inhibitor; Fig. 5) was necessary to express inhibitory activity.35) It seems reasonable to assume that this arginine residue might contribute towards binding to a target site on the a-amylase molecule because it occurs in the portion highly conserved among proteinaceous a-amylase inhibitors, while the specificity of the inhibitor towards a-amylases should be attributed to amino acid residues in the carboxy-terminal half, which are not so highly conserved.…”
Section: Discussionmentioning
confidence: 99%
“…The isolation and some properties of T -76 inhibitor were described in our previous report. 6) The structural genes of Haim 16,17) and Tendamistat 1S ) have been cloned and characterized. It is important to clone the other inhibitor genes and make their primary structures clear so as to obtain more information on the relationship between inhibitory specificity and amino acid sequence.…”
mentioning
confidence: 99%
“…lividans, the gene products are typically secreted (5,8,12,15,25,29,34). In some cases, the site for signal sequence processing in S. lividans was demonstrated to be identical to that for processing in the native host strain (8,25).…”
mentioning
confidence: 99%